IMPLEMENTATION OF FILMORAGO IN THE VIDEO SCREENING PROGRAM "SUNGAIKU INDAH" AT KKNM CITARUM HARUM - Erwin Yulianto; Siti Anah Kunyati, Irwin Supriadi (JOURNAL OF COMMUNITY DEDICATION, 2025)
Several problems with the Citarum River include damage to land in the watershed, deteriorating water quality as a result of pollution, and uncontrolled use of water space. Pollution comes from agricultural and livestock activities, as well as domestic and industrial waste. The Student Real Work Lecture (KKNM) themed Citarum Harum is a Community Service (PKM) activity carried out Cikutra Village, Cibeunying Kidul District, Bandung City as the implementation of the Tri Dharma of Higher Education. The implementation of this PKM uses descriptive methods where data collection is done using observation, interviews, and literature studies. Other methods used are discussion, outreach, and demonstration. The programs carried out include the observation of Cikutra River, the socialization of the Citarum Harum program material launched by the Environment Agency, and the making of the "Sungaiku Indah" Video Screening. Based on observations, the "Sungaiku Indah" Video Screening program which involved all village officials and the Cikutra community was able to increase awareness in maintaining Cikutra River in supporting the Citarum Harum program.